Szolnoki Ságvári körúti Általános Iskola Ságvári Videóstúdiója
exercise for pupils, technology, presenting sites and work procedures, paper technology, Szolnok paper factory, Sándorné Balázs, Ferenc Koncsek, Istvánné Sulák